Risk factors and impact on outcomes of high-density shadow on immediate cerebral CT after successful interventional recanalization in acute ischemic stroke with large vessel occlusion - Zhang, Wensheng; Xing, Weifang; Feng, Jiyun; Wen, Yangchun; Zhu, Minzhen; Lan, Haiping; Zhong, Xiaojing; Jiang, Zhenqin; Ling, Li (Frontiers in Neurology, 2025)
ObjectiveTo explore the risk factors, classification, relation with hemorrhage and clinical significance of high-density shadow on immediate cerebral CT in patients with large vessel occlusion acute ischemic stroke after successful interventional recanalization.MethodsA retrospective analysis was conducted on patients with acute ischemic stroke due to anterior circulation large vessel occlusion who received interventional recanalization from January 2019 to December 2023 in Heyuan People’s Hospital. The main inclusion criteria included NIHSS score ≥ 6 points at the time of onset, the time from onset to femoral artery puncture ≤ 24 h and so on. The main exclusion criteria included pre onset mRS score > 2 points, the vital signs were unstable during the onset of the disease and so on. Variables we studied included NIHSS score at admission, preoperative ASPECT score, blood flow reperfusion eTICI grading, surgical methods and so on. According to the distribution, density, volume, etc. of cerebral hyperdensity, high-density shadow was divided into cortical type, soft type, metallic type, and diffuse type.Results318 patients showed high-density shadow on cerebral CT immediately after successful interventional recanalization. In multiple logistic regression analysis, the history of hypertension and preoperative ASPECT score were correlated independently with the occurrence of high-density shadow. 27 patients experienced symptomatic intracranial hemorrhage. It was found that high-density shadow was not independent with symptomatic intracranial hemorrhage in univariate logistic regression analysis (p > 0.05). In the classification of high-density shadow, there were 16 cases of cortical type, 85 cases of soft type, 80 cases of metallic type, and 137 cases of diffuse type. Patients with diffuse type had the highest incidence of futile recanalization, symptomatic intracranial hemorrhage, malignant brain edema, and highest mortality rate within 3 months after surgery (p < 0.05).ConclusionA low preoperative ASPECT score was an independent risk factor of high-density shadow on immediate cerebral CT after successful interventional recanalization, while a history of hypertension, mere use of balloon angioplasty and combination of balloon angioplasty and stent implantation may serve as a protective factor. Patients with diffuse high-density shadow had the worst prognosis and the highest incidence of symptomatic intracranial hemorrhage and malignant brain edema.